COMPARISON OF NAHWU LEARNING WITH THE JURUMIYAH BOOK AT DURROTU ASWAJA ISLAMIC BOARDING SCHOOL AND ATSAQOFAH ISLAMIC BOARDING SCHOOL SEMARANG - Muhammad Faisal Amritama; Maulida Zahra Qutratu’ain; Ruwaidah Taleh (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This study aims to analyze the comparative learning of nahwu (Arabic grammar) using the Kitab Jurumiyah at Durrotu Aswaja Islamic Boarding School and Atsaqofah Islamic Boarding School in Semarang. The research is motivated by the importance of nahwu as a discipline for understanding Arabic texts, especially the classical ‘kitab kuning,’ and the characteristics of instructional approaches in each pesantren. The study employs a qualitative approach using a comparative case study method. Data were collected through observation, interviews, documentation, and tests, and were analyzed using the Miles and Huberman model, which involves data collection, data reduction, data presentation, and conclusion drawing. The findings indicate that the teaching of nahwu in both pesantren shares similarities in the use of the Kitab Jurumiyah as a foundational text, but differs in aspects of planning, implementation, and evaluation. Durrotu Aswaja Islamic Boarding School adopts a structured system of planning and evaluation, whereas Atsaqofah Islamic Boarding School emphasizes flexibility and a communicative learning environment. Both institutions retain traditional pesantren learning methods with a teacher-centered approach, utilizing the bandongan and sorogan methods. This research demonstrates that learning nahwu through the Kitab Jurumiyah remains relevant for building students’ Arabic language skills, but highlights the need for the development of methods and evaluation systems to make instruction more effective and adaptive to the needs of education.